Empowering Data Sovereignty: Decentralized Image Sharing through Blockchain and Interplanetary File System - Vayadande, Kuldeep; Singh, Viomesh; Sultanpure, Kavita; Deshpande, Deepali; Patil, Harshwardhan; Patil, Aditya; Pathak, Ameya; Pareek, Shyam; Patil, Darshan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The current digital environment poses challenges because of the widespread dependence on centralized systems, which create a single weak point and expose data to risks. The need for a central authority to manage data raises questions about data access, protection, and confidentiality. To address these challenges, our research presents an innovative paradigm—a meticulously architected decentralized image-sharing platform leveraging blockchain technology and the Interplanetary File System (IPFS). We use the IPFS protocol, backed by the reliable Pinata IPFS gateway, to ensure the integrity and availability of data and to store files securely and wisely. Our system is based on removing the need for a central authority to control content sharing and giving users full sovereignty over their data. Every transaction on the platform creates a unique hash, which is carefully stored in the blockchain’s smart contract. Our research decentralizes the existing image-sharing model and leverages blockchain and IPFS features to enhance security, transparency, and privacy. This decentralized image-sharing platform marks a new era of content distribution and management, strengthening data protection and privacy and empowering users. The amalgamation of blockchain technology and IPFS imparts an avant-garde character to the platform, serving as an efficacious solution to exigent issues related to centralized data management, upholding sacrosanct principles of user privacy and data ownership.